1989
DOI: 10.1177/014920638901500204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Operations Management from a Strategic Perspective

Abstract: Manufacturing strategy research, together with service operations and strategy research, form the background for an examination of operations management. Although much of the assessment and critique is directed at operations strategy, traditional operations management issues such as technology, productivity, and quality also come under scrutiny as to their role in strategy. This review identifies three common themes and seven missing themes in the literature, contrasting the "'content" variables so frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
0
8

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(165 citation statements)
references
References 34 publications
1
156
0
8
Order By: Relevance
“…Hence, it is important to pay special attention to the characteristics of the service sector and also to the customers' feelings that distinguish it from traditional manufacturing (Lee, 2009). Services, compared to manufacturing, involve the conversion of resources into an "intangible" output (Adam and Swamidass, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is important to pay special attention to the characteristics of the service sector and also to the customers' feelings that distinguish it from traditional manufacturing (Lee, 2009). Services, compared to manufacturing, involve the conversion of resources into an "intangible" output (Adam and Swamidass, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the closeness of the service business to customers, service operations must be extremely sensitive to customers and markets (Adam and Swamidass, 1989) and achieving customer satisfaction is a challenge in the service sector.…”
Section: Introductionmentioning
confidence: 99%
“…Worksheets are written documents that enable accessibility of data, papers and decisions to the participants (Platts, 1994). Adam and Swamidass (1989) used infrastructure, manufacturing task and order winning criteria as process variables, here called competitive priorities and decision areas. It is essential that both intangible and tangible competitive priorities are included in a framework (Platts et al, 1998).…”
Section: Assessment Criteriamentioning
confidence: 99%
“…Finally, a firm adopting a broad differentiation strategy strives to provide a wide range of services to a variety of target markets. Although the dominant paradigm for structuring operations management strategy has been established in a manufacturing environment (Menor et al, 2001), these broad configurations appear to be applicable in service organisations (Adam and Swamidass, 1989). Indeed, variables developed for service strategy research have paralleled the ones found in the traditional manufacturing strategy literature (Roth et al, 2008).…”
Section: Customer Inputsmentioning
confidence: 99%